Medical Humanities in the Nepalese context - Shankar, Pathiyil Ravi (Journal of Nepal Health Research Council, 2021)
Medical humanities use the creative and intellectual strengths of the arts for specific purposes in medical education. The author read with great interest the Medical humanities program at the Patan Academy of Health Sciences and has been associated with Medical humanities since 2007. There are several factors favouring the development of Medical humanities in Nepal but the major challenge is there is no specific faculty and/or department involved and the discipline may be relegated to the background in the face of other pressing priorities. In the west humanities faculty had played an important role in popularizing Medical humanities. Clinical teachers can incorporate Medical humanities into their clinical teaching. Large student sizes and lesser number of faculty may be challenges in moving the discipline forward. Keywords: Medical humanities, medical schools, Nepal, undergraduate medical